Age and sex variation in the distribution of visceral fat among healthy doctors - Joy, Anusha Maria; Panchu, Pallavi; Bahuleyan, Biju; Vijayan, Vineetha; Jojy, John (International Journal of Research in Medical Sciences, 2018)
Background: Non Communicable Diseases (NCDs) are a mushrooming problem and accounts for majority of deaths. Paradoxically the population of Kerala is increasingly susceptible to NCDs despite having good access to health care. Doctors work in highly stressful conditions and often adopt sedentary lifestyles thereby forming a subset of the NCD prone population. The objective of this study was to assess the health status of the doctors which would provide an insight into their health and level of awareness regarding the role of lifestyle in prevention of NCDs. Methods: Sixty five doctors participated in this Cross-Sectional Observational study conducted at a CME in Kerala. After obtaining Institutional Ethical clearance, demographic profile was collected, and fat levels were estimated using body composition analyzer (OMRON-HBF375). The results were tabulated using Microsoft Office Excel, analyzed using SPSS version 20. Results: On classifying the study group based on BMI, only 34 were normal, 26 were Overweight, and 4 were Obese. Gender wise distribution of body fat revealed only 4 had normal body fat composition. The study also showed that as age advances the amount of total and visceral fat shows a significant upward trend in males. Conclusions: BMI alone cannot be used as a predictor of health status. Body Fat percentage analysis should be included in routine screening programs. Men have a tendency to develop visceral adiposity with age. Females depend more on fat as primary source and hence females will respond better to a properly programmed exercise regime and men to a well guided diet program with exercise.